Propaganda Bust and Painting (photo) of Hitler Defaced damaged after... - Adam Jones (Wikimedia Commons, 2022)
Notice iconographique issue de Wikimedia Commons. Titre: Propaganda Bust and Painting (photo) of Hitler Defaced damaged after WW2 Liberation 1945. Caen Memorial, Normandy, France. Museum exhibits. Adam Jones 2022-06-7 Flickr. Bust and propagandistic portrait photo and of Adolf Hitler, leader of Nazi Germany, deliberately defaced during the liberation of France in World War II. Photo taken by Adam Jones 2022-06-07 of the exhibitions at Mémorial de Caen, a museum and war memorial in Caen, Normandy, France commemorating World War II and the Battle for Caen.
Licence Creative Commons Attribution 2.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; photographie